Pattern Dynamics of Vegetation Growth With Saturated Water Absorption - Li, Li; Cao, Jia-Hui; Bao, Xin-Yue (Frontiers in Physics, 2021)
Regular pattern is a typical feature of vegetation distribution and thus it is important to study the law of vegetation evolution in the fields of desertification and environment conservation. The saturated water absorption effect between the soil water and vegetation plays an crucial role in the vegetation patterns in semi-arid regions, yet its influence on vegetation dynamics is largely ignored. In this paper, we pose a vegetation-water model with saturated water absorption effect of vegetation. Our results show that the parameter $1/P$, which is conversion coefficient of water absorption, has a great impact on pattern formation of vegetation: with the increase of $P$, the density of vegetation decrease, and meanwhile it can induce the transition of different patterns structures. In addition, we find that the increase of appropriate precipitation can postpone the time on the phase transition of the vegetation pattern. The obtained results systematically reveal the effect of saturated water absorption on vegetation systems which well enrich the findings in vegetation dynamics and thus may provide some new insights for vegetation protection.